Control of Nonlinear Chemical Processes Using Adaptive Proportional-Integral Algorithms - Ali, Emad (Industrial & engineering chemistry research, 2000)
It is believed that a fixed-parameter proportional-integral derivative (PID) may not do well for nonlinear, time-variant, or coupled processes. It needs to be re-tuned adequately to retain robust control performance over a wide range of operating conditions. Alternatively, nonlinear control algorithms can be employed. To avoid complexity introduced by such nonlinear controllers, modified PID algorithms that have the ability to adapt their tuning parameters on-line can be used instead to perform as well. An automatic on-line tuning strategy for PI controllers is proposed and compared with other existing adaptive PI algorithms such as fuzzy gain scheduling, model-based gain scheduling, a nonlinear version of PI, internal model control, and self-tuning adaptive control. The proposed tuning methodology adapts the PI settings by direct utilization of explicit expressions for the gradients of the closed-loop response with respect to the PI settings. The adapted parameters are determined such that the resulting closed-loop response lies inside predefined time-domain constraints. Application of the proposed technique as well as the other aforementioned systems to two nonlinear simulated continuously stirred tank reactor examples is demonstrated. These examples present challenging control problems because of their interesting dynamics such as time-varying gain and gain with changing sign character. Simulation results indicated that the proposed tuning algorithm can provide comparable, if not superior, performance to those obtained by the other tested algorithms.